Solusi Berkelanjutan untuk Lingkungan Bersih melalui Pengelolaan Limbah Organik Rumah Tangga - Sudarmaji, Imam; Saepuloh, Dadang; Sabur, Ambuy; Fahmi, Rizal; Ramdani, Heni Cahya (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2025)
The community empowerment program on household organic waste management in Kampung Kebon Cau, Indonesia, aimed to promote sustainable waste management practices through environmental education, simple composting technology, and small-scale entrepreneurship. Using participatory methods, community members received training, composting tools, and post-implementation mentoring. The results revealed significant improvements in participants’ understanding and skills in composting, with an adoption rate exceeding 80% and a 55% reduction in organic waste volume. Participating households also experienced enhanced environmental cleanliness through the use of compost and Aloe vera-based products. Socially, the initiative fostered collective environmental responsibility and strengthened the local green economy. The program demonstrates that integrating community-based education with low-cost technology can effectively reinforce circular economy practices and support Sustainable Development Goals (SDGs) 12 (Responsible Consumption and Production) and 13 (Climate Action). The findings contribute to the growing literature on community-based sustainable waste management and offer a replicable model for rural, urban, and semi-urban contexts, with potential for integration into digital monitoring systems to ensure long-term sustainability.